Beta-lapachone: Natural occurrence, physicochemical properties, biological activities, toxicity and synthesis. (June 2021) - Gomes, Camila Luiz; de Albuquerque Wanderley Sales, Victor; Gomes de Melo, Camila; Ferreira da Silva, Rosali Maria; Vicente Nishimura, Rodolfo Hideki; Rolim, Larissa Araújo; Rolim Neto, Pedro José
Abstract: β-Lapachone is an ortho -naphthoquinone originally isolated from the heartwood of Handroanthus impetiginosus and can be obtained through synthesis from lapachol, naphthoquinones, and other aromatic compounds. β-Lapachone is well known to inhibit topoisomerase I and to induce NAD(P)H: quinone oxidoreductase 1. Currently, phase II clinical trials are being conducted for the treatment of pancreatic cancer. In view of ever-increasing scientific interest in this naphthoquinone, herein, the authors present a review of the synthesis, physicochemical properties, biological activities, and toxicity of β-lapachone. This natural compound has shown activity against several types of malignant tumors, such as lung and pancreatic cancers and melanoma. Furthermore, this ortho -naphthoquinone has antifungal and antibacterial activities, underscoring its action against resistant microorganisms and providing anti-inflammatory, antiobesity, antioxidant, neuroprotective, nephroprotective, and wound-healing properties. β-Lapachone presents low toxicity, with no signs of toxicity against alveolar macrophages, dermal fibroblast cells, hepatocytes, or kidney cells. Graphical abstract: Image 1 Highlights: The formation of ROS is the primary mechanism of β-lapachone against cancer cells. The β-lapachone has shown antiviral, antiparasitic and antimicrobial effects. Anti-inflammatory activities of β-lapachone may be due to synergistic mechanisms. β-lapachone has potential therapeutic effects on obesity by the fat-browning effect. β-Lapachone is able to suppress metastasis in vivo by several mechanisms.